Investigation of chicken housekeeping genes using next-generation sequencing data - Hasanpur, Karim; Hosseinzadeh, Sevda; Mirzaaghayi, Atiye; Alijani, Sadegh (Frontiers in Genetics, 2022)
Accurate normalization of the gene expression assays, using housekeeping genes (HKGs), is critically necessary. To do so, selection of a proper set of HKGs for a specific experiment is of great importance. Despite many researches, there is no consensus about the suitable set of HKGs for implementing in the quantitative Real-Time PCR analyses of chicken tissues. A limited number of HKGs have been widely used. However, wide utilization of a little number of HKGs for all tissues is challenging. Emerging of high-throughput gene expression RNA-Seq data has enabled the comparison of the stability of multiple HKGs, simultaneously. Therefore, employing the average coefficient of variations of at least three datasets per tissue, we sorted all reliably expressed genes (REGs; with FPKM=>1 in at least 1 sample) and introduced top-10 most suitable, stable reference genes for each of the 16 chicken tissues. We evaluated the consistency of the results of five tissues using the same methodology on other sets of datasets. Furthermore, we assessed 96 previously widely used HKGs (WU-HKGs) in order to challenge the accuracy of the previous researches. New-tuxedo software suite was used for the main analyses. The results revealed novel, different sets of reference genes for each of the tissues with 17 common genes among the top-10 genes’ lists of 16 tissues. The results did disprove the suitability of WU-HKGs such as Actb, Ldha, Scd, B2m and Hprt1 for any of the tissues examined. On the contrary, a total of 6, 13, 14, 23, and 32 validated housekeeping genes (V-HKGs) were discovered as the most stable, suitable reference genes for muscle, spleen, liver, heart and kidney tissues, respectively. Although we identified a few new HKGs for usable for multiple tissues, the selection of suitable HKGs is required to be tissue specific. The newly introduced reference genes from the present study, despite lacking experimental validation, will be able to contribute to the more accurate normalization for future expression analysis of chicken genes.